DIGITAL FORENSICS IN MARTIAL LAW - Holdberh, Natalia; Kolonska, Viktoriya (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the article is to study a new area of forensics - digital forensics. Research methods: the article uses the hermeneutic method, the method of classification, logical methods (analysis, synthesis, induction, deduction, generalization, etc.), and the method of systematization. Results: the article explores a new branch of forensics, namely digital forensics. Digital forensics is becoming increasingly important and is becoming one of the main components of traditional forensics. Knowledge of digital forensics is used in many investigative actions and in the process of appointing relevant forensic examinations not only in relation to offenses in the field of information technology, but also in the investigation of a wide range of crimes committed during the war and occupation. Discussion: the author analyzes the views of leading scholars on the concept of digital forensics in the system of forensic science. The author assesses the trends in the development of digital forensics at the present stage and predicts the further development of this area in Ukraine, and conducts a legal analysis of the use of digital forensics. The existing model of forensic science in Ukraine urgently requires the formation of a separate branch of forensic technology, which includes means and methods of digital evidence investigation. The article also examines the peculiarities of digital forensics application under martial law. In particular, new challenges and opportunities arising from the active use of digital technologies in modern conflicts are analyzed.